Pengaruh Metode Karyawisata Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS - Wurdjinem Wurdjinem; Pebrian Tarmizi; Tika Oktaviana (Universitas Bengkulu, 2018)
The aim of this study was to find out the influence of study tour method of students' learning output to the social subject. This was a quantitative research with an experiment method, in design of The Matching Only Pretes-Posttest Control Group Design which was implemented in class IVSDN 74 Kota Bengkulu. The population of this research was the students in class IV SDN 74 Kota Bengkulu which were 137 students. The sample was taken by applying Cluster Random Sampling technique or simple randomly, so that it had class IV A which had 34 students as the experiment class, while class IV B with 34 students as the control class. The data was collected by using Pretest-Posttest tecniques as much 25 optional questions. The data gathered was analyzed by descriptive analysis, prerequisite test, and hypotheses test. Based on the hypotheses test by using t-test, the result was t test 2,315 > t tabel 2,00 in ghe significancy level of 5% which meant that the Ha alternative was accepted and Ho was rejected. It meant, there was an Influence of study tour method of students' learning output to the social subject.